ANALISIS PENGUKURAN WAKTU KERJA KARYAWAN BENGKEL TOYOTA AUTO 2000 Di BALIKPAPAN - -, Agus - (EKONOMIA, 2014)
This study aims to determine the specific labor standard time engine oil replacement vehicle machine Toyota Auto 2000 MT. Balikpapan Haryono used standard working time. Based on interviews with employees of Auto 2000 Toyota workshop. MT. Haryono completed replacement of engine oil required an average completion time of 1 hour of receipt to the consumer.The problem of this study is the labor time required to complete the work car oil changes are in accordance with the standart time in the workshop of Toyota Auto 2000 MT. Haryono Balikpapan.The theory used by the researchers is the operational management as an activity pengcordination production process to increase the usefulness (utility) of goods or services. The hypothesis of this study is the labor time required to do the oil change time is much longer than the standart time in the workshop of Toyota Auto 2000 MT. Haryono Balikpapan. The data has been collected in the study analysis using standard working time. The formula used to calculate the standard working time study = .The average time oil changes machine Toyota Auto 2000 MT. Haryono Balikpapan observations of 30 times by 81 minutes or 1 hour 21 minute. Normal time oil changes machine Toyota Auto 2000 MT. Haryono Balikpapan is 81 minutes or 1 hour 21 minutes. Time standard oil change machine Toyota Auto 2000 MT. Haryono Balikpapan to leniency factor of 5% of the normal time is 85 minutes or 1 hour 25 minutes.The results of the analysis and discussion showed that the labor time in doing oil changes machine Toyota Auto 2000 MT. Haryono Balikpapan longer than the standard working time according to the workshop of Toyota Auto 2000 MT. Haryono, labor time doing oil changes machine Toyota Auto 2000 MT. Haryono Balikpapan which is larger than the standard time in the workshop of Toyota Auto 2000 MT. Haryono ie 1 hour, with this hypothesis is accepted.